2008
DOI: 10.1183/09031936.00166407
|View full text |Cite
|
Sign up to set email alerts
|

Higher pulmonary artery pressure in children than in adults upon fast ascent to high altitude

Abstract: The response of pulmonary artery pressure to high altitude has not been studied in children. It is also not known whether the individual response is hereditary. Therefore, the response of pulmonary artery pressure to high altitude was measured in pre-pubertal children in comparison to that in their biological fathers.Echocardiography was performed at 450 m and over 3 days at 3,450 m. Systolic pulmonary artery pressure was estimated from the pressure gradient of tricuspid regurgitation.The increase in pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…It is tempting to speculate that in the present study, intact alveolar fluid clearance may have prevented HAPE in children with exaggerated hypoxic pulmonary hypertension. A previous small study (17) suggested that after rapid ascent to this altitude the increase of pulmonary artery pressure was maximal a few h after arrival. Here, we could not confirm this finding, since pulmonary artery pressure was comparable 4 -6, 18 -20, and 40 h after arrival.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is tempting to speculate that in the present study, intact alveolar fluid clearance may have prevented HAPE in children with exaggerated hypoxic pulmonary hypertension. A previous small study (17) suggested that after rapid ascent to this altitude the increase of pulmonary artery pressure was maximal a few h after arrival. Here, we could not confirm this finding, since pulmonary artery pressure was comparable 4 -6, 18 -20, and 40 h after arrival.…”
Section: Discussionmentioning
confidence: 96%
“…Surprisingly, in children and adolescents there is very little information on cardiovascular adjustments to acute high altitude exposure (26). A recent small study (17) suggests that the initial altitude-induced increase of pulmonary artery pressure is more pronounced in children than in their fathers. We speculated that if confirmed this exaggerated increase of pulmonary artery pressure could suggest that the risk of developing HAPE and acute right ventricular pressure overload may be greater in children than in adults.…”
mentioning
confidence: 97%
“…These novel findings suggest that the hypoxemia experienced by COPD patients going to an altitude as encountered in many tourist destinations or during commercial air travel is causing considerable impairment of the pulmonary and systemic circulation that may possibly contribute to exercise limitation or even predispose to cardiac failure. In the literature, many previous studies observing effects of acute exposure to hypobaric or normobaric hypoxia have described increases in PAP in healthy subjects: Kriemler et al [21] performed an echocardiographic field study on 20 healthy individuals (mean age 44 years) and revealed an increase in mean sPAP from 24 mm Hg at 450 m to 32 mm Hg on the first day at 3,450 m. Similar results from younger study collectives have been reported by several other authors describing sPAP values ranging from 30 ± 6 mm Hg at 3,730 m to 41 ± 3 mm Hg at 5,000 m [22][23][24][25][26][27][28]. Thus, with an estimated sPAP of 28 mm Hg (24; 35) at 490 m, the current COPD patients already started with higher pressures at low altitude when compared to healthy subjects, and furthermore showed a greater increase when ascending to 2,590 m; such values were reported for healthy subjects only at very high altitudes (> 4,500 m) [22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…21.1 ). Their relatives have not been studied, but children and their fathers at 3,450 m show similar PA pressure increases [ 26 ], suggesting HPV is, in part, genetically determined as is the hypoxic ventilatory response (HVR) [ 27 ]. The prevalence of heightened pulmonary vascular responsiveness in the general population may be as high as 10 % [ 28 ] and may contribute to the out of proportion pulmonary hypertension that develops later in life in patients with sleep apnea, heart failure, and chronic lung disease.…”
mentioning
confidence: 74%